Orientation-reversal and phase-reversal visual evoked potentials in full-term infants with brain lesions: a longitudinal study. - Mercuri, E; Braddick, O; Atkinson, J; Cowan, F; Anker, S; Andrew, R; Wattam-Bell, J; Rutherford, M; Counsell, S; Dubowitz, L (1998)
The onset and maturation of visual cortical mechanisms can be recorded by using steady-state visual evoked potentials. The aim of this study was to evaluate and compare orientation-reversal (OR) and phase-reversal (PH) VEP as indicators of the maturation of cortical function in a population of fullterm infants with brain lesions on neonatal MRI. Forty-six infants with brain lesions on neonatal MRI were tested on both PH and OR VEP at 8 reversals/second at the age of 5 months and, if the responses were not significant, at a lower temporal frequency (4 reversals/second). Children whose VEPs were not significant at 5 months were tested longitudinally at 6, 9, 12 and 18 months. The results showed that 23 of the 46 infants (50%) did not show significant responses at 5 months and that while in 7 of the 23 (14% of the whole cohort) the responses became significant between 5 and 12 months, in the other 16 infants (34%) the VEP responses were persistently abnormal. Children with focal lesions, such as focal infarction or haemorrhages, tended to show normal or only mildly delayed VEP while more generalised lesions, such as the ones seen in infants with hypoxic-ischaemic encephalopathy grade 2 and 3, tended to be associated with abnormal VEP responses. The involvement of the optic radiations and occipital cortex was not always associated with abnormal VEP responses but the concomitant involvement of the basal ganglia was always associated with abnormal VEP. We were also able to demonstrate that VEP can be also used as a prognostic indicator: while normal OR VEP are reliably associated with a normal visual and neurodevelopmental outcome, abnormal 4 OR or 8 PH at 5 months are consistently associated with abnormal outcome.